An introduction to International investment law - Collins, David, 1975- (Cambridge : Cambridge University Press, 2017)
This insightful and accessible introduction provides students and practitioners with a comprehensive overview of the increasingly important discipline of international investment law. Focusing primarily on the legal principles contained in the growing body of international investment agreements, this book covers the core concepts of the discipline with attention given to their relation to each other and to the manner in which they have been developed through arbitration case law. The context of each legal principle is explored along with a consideration of some of the major debates and emerging criticisms. Avoiding extensive case extracts, this book adopts an engaging and succinct narrative style which allows readers to advance their understanding of the topic while examining the legal principles with academic rigour and discerning commentary.
Title from publisher's bibliographic system (viewed on 29 May 2018).
Keywords: elektronické knihy; electronic books; Investments, Foreign -- Law and legislation; Investments, Foreign (International law)